Genomic and transcriptomic changes complement each other in the pathogenesis of sporadic Burkitt lymphoma - López, Cristina; Kleinheinz, Kortine; Hübschmann, Daniel; Raimondi, Francesco; Russell, Robert B.; Eils, Roland (Nature Communications, 2019)
Burkitt lymphoma (BL) is the most common pediatric B-cell lymphoma. Here, within the International Cancer Genome Consortium, the authors performed whole genome and transcriptome sequencing of 39 sporadic BL, describing the landscape of mutations, structural variants, and mutational processes that underpin this disease how alterations on different cellular levels cooperate in deregulating key pathways and complexes.